Research on the impacts and mechanisms of digital strategy on corporate innovation investment - Dong Yang; Huayu Shen (Journal of Open Innovation: Technology, Market and Complexity)
This paper empirically examines the impacts and underlying mechanisms of a digital strategy, along with its four constituent indicators, on enterprise innovation investment. Utilizing a vast sample of companies listed on Chinese stock markets spanning from 2007 to 2022, the study constructs measurement indices for enterprise digital strategies through rigorous text analysis. A multitude of analytical techniques, including panel fixed effects regression, panel mediation effects regression, panel moderation effects regression, and two-stage instrumental variable regression, are employed to investigate these impacts. The findings reveal that a digital strategy exerts a significant and positive influence on firm innovation investment. Furthermore, the mechanism through which this impact occurs is elucidated: digital strategy fosters company innovation investment by augmenting investments in R&D human capital and digital infrastructure. Heterogeneity analysis underscores that the implementation of a digital strategy has a more pronounced effect on company innovation investment under conditions of high financial constraints. Conversely, when institutional investors hold a larger proportion of shares, the impact of digital strategy implementation on company innovation investment is less pronounced. The robustness of these findings is confirmed through additional tests, such as two-stage instrumental variable regression, a panel random effects model, and substitution of the dependent variable. These results collectively offer a scientific rationale for companies to adopt digital strategies and enhance their innovation investment endeavors.